A Model of the Commitment to Change in Higher Education - Erika Setyanti Kusumaputri; Fathul Himam; Tina Afiatin; IJK Sito Meiyanto (ANIMA Indonesian Psychological Journal, 2014)
The purpose of this study was to find out the correlation between the theoretical model of the organization’s capability contribution, participation, and the climate of change to the commit-ment to change. Subjects were Islamic University lecturers in Indonesia who experienced the organizational change. Findings reveal (a) the theoretical model designed in this study fitted the empirical data; (b) the determination coefficient (R2) of the commitment to change was 15.1%, which showed that 15.1% of the commitment to change can be explained or predicted through the organization’s capability, participation, the climate of change and the open-mindedness to changes variables; (c) the model was acceptable based on the fit model test with 60.785 chi-square value and .275 (> .05) probability, the CFI value was .997 (almost 1), and the RMSEA value was .022 (< .08). This study has found out the determining theoretical model of the commitment to change based on the organization’s capability, participation, the climate of change, and the open-mindedness to changes’ roles in establishing the commitment to change. The open-mindedness to changes as a mediator is significant, because without the mediator, the organization’s capability, participation, and the climate of change have no effects to the commitment to change.